2000
DOI: 10.1046/j.1365-313x.2000.00905.x
|View full text |Cite
|
Sign up to set email alerts
|

A new hyperrecombinogenic mutant of Nicotiana tabacum

Abstract: SummaryWe have isolated a hyperrecombinogenic Nicotiana tabacum mutant. The mutation, Hyrec, is dominant and segregates in a Mendelian fashion. In the mutant, the level of mitotic recombination between homologous chromosomes is increased by more than three orders of magnitude. Recombination between extrachromosomal substrates is increased six-to ninefold, and intrachromosomal recombination is not affected. Hyrec plants were found to perform non-homologous end joining as ef®ciently as the wild type, ruling out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 48 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…To address this question, a genetic screen for Arabidopsis mutants in which the frequency of HR is upregulated was undertaken. Although recombination mutants have been isolated previously, the nature of most of the affected genes has not been studied (Masson and Paszkowski, 1997;Gorbunova et al, 2000;Lucht et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…To address this question, a genetic screen for Arabidopsis mutants in which the frequency of HR is upregulated was undertaken. Although recombination mutants have been isolated previously, the nature of most of the affected genes has not been studied (Masson and Paszkowski, 1997;Gorbunova et al, 2000;Lucht et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The potential for homologous recombination has been evaluated in plants by using a transgene cassette that consists of two nonfunctional copies of the luciferase gene that contained 1,146 bp of overlapping sequence (Gorbunova et al, 2000;Kovalchuk et al, 2003). The restoration of luciferase function was visualized as bright spots on the leaves and indicated that a homologous recombination event had led to the excision of the duplicated portion of the luciferase gene.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yao et al (2011) reported that they employed a 500 bp noncoding DNA fragment as linker. However, after consulting the references cited, we found that the linker sequence used in their study in fact appears to be much larger and contains the bar gene cassette providing resistance to phosphinothricin (Gorbunova et al, 2000). Van der Auwera et al (2008) used mannopine synthase promoter and enhancer elements as the linker sequence but they considered this information and sequence details irrelevant to their study (Van der Auwera et al, 2008).…”
Section: Linker Dna: a Critical Element That Has Been Overlookedmentioning
confidence: 99%
“…sequences having 29 amino acids of the open reading frame V of CaMV (Swoboda et al, 1994) or the omega (V) enhancer of Tobacco mosaic virus (Gorbunova et al, 2000) (Figure 1). These fragments are believed to enhance transgene protein production up to a level necessary to visualize clonal GUS (Schultze et al, 1990) or LUC spots.…”
Section: Cryptic Introns and Promoters In Luc Or Gus Fragmentsmentioning
confidence: 99%